1996
DOI: 10.4319/lo.1996.41.2.0197
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of trace elements and carbon by the mussel Mytilus edulis: Effects of food composition

Abstract: Assimilation efficiency (AE) is an important physiological parameter in determining trace element influx from food sources into aquatic animals. We used radiotracer techniques to examine the influence of diet [seven species of algae (two diatoms, two chlorophytes, a prasinophyte, and two dinoflagellates) and glass beads] on the assimilation of seven trace elements (Ag, Am, Cd, Co, Cr, Se, Zn) and C in the mussel Mytilus edulis. Trace element assimilation was related to C assimilation and cytoplasmic distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
191
8

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(227 citation statements)
references
References 46 publications
28
191
8
Order By: Relevance
“…Maximum 'OqCd-AES occurred at a DQ of 60%) for just algae and at a DQ of 33% for 25 mg 1-' SPM, where maximum C-AEs for this species have been previously noted. This relationship supported the previous findings of Wang & Fisher (1996b), who noted a positive relationship between carbon assimilation and ""Cd-AE for the filter-feeding blue mussel.…”
Section: '09cd Assimilation Efficiencysupporting
confidence: 82%
“…Maximum 'OqCd-AES occurred at a DQ of 60%) for just algae and at a DQ of 33% for 25 mg 1-' SPM, where maximum C-AEs for this species have been previously noted. This relationship supported the previous findings of Wang & Fisher (1996b), who noted a positive relationship between carbon assimilation and ""Cd-AE for the filter-feeding blue mussel.…”
Section: '09cd Assimilation Efficiencysupporting
confidence: 82%
“…The present study indicated that fish might be bioassimilating Pb from anthropogenic sources such as atmospheric deposits suspended in water columns. Previous studies have also reported that the highest trace metal concentrations in fish were found in their gills (Eisler, 1979;Wang and Fisher, 1996;Barata et al, 2002). This issue can be further investigated in the future by examining the differences in the Pb isotopic composition in the gills, livers, stomachs and fleshes of fish.…”
Section: Stable Pb Isotope Compositions In Aquatic Organismsmentioning
confidence: 87%
“…Trace metal assimilation efficiency varies with food items. It has been reported that assimilation efficiency differed by up to fivefold for Se, ninefold for Ag, and 10-fold for Cr(VI) in mussels feeding on different food particles [43]. The assimilation efficiencies of Cr (III) bound with bacteria and phytoplankton could also be 20-fold different for clams M. balthica [2].…”
Section: Bioaccumulation Ofmentioning
confidence: 99%